2020
DOI: 10.1002/cpdd.867
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double‐Blind, Placebo‐ and Positive‐Controlled, 4‐Period Crossover Study of the Effects of Solriamfetol on QTcF Intervals in Healthy Participants

Abstract: Solriamfetol, a dopamine and norepinephrine reuptake inhibitor, is approved (United States and European Union; Sunosi) to treat excessive daytime sleepiness associated with narcolepsy (75-150 mg/day) or obstructive sleep apnea (37.5-150 mg/day). A thorough QT/QTc study assessed solriamfetol effects on QT interval (Fridericia correction for heart rate; QTcF). This randomized, double-blind, placebo-and positive-controlled, 4-period crossover study compared single doses of 300 and 900 mg solriamfetol, 400 mg moxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…23 In a randomized, double-blind, fourperiod, placebo-and positive-controlled crossover study, the effects of solriamfetol 300 mg and 900 mg on QTc interval were studied and demonstrated minimal risk of QTc prolongation. 50 The FDA's review of this study concluded that a dose of 300 mg of solriamfetol (which is twice the highest FDA-approved dose) did not prolong the corrected QT interval by Fredericia (QTcF) to a clinically relevant extent. 1 There were no deaths with solriamfetol use in the 12week trials (TONES 2 and 3).…”
Section: Safety and Tolerabilitymentioning
confidence: 88%
“…23 In a randomized, double-blind, fourperiod, placebo-and positive-controlled crossover study, the effects of solriamfetol 300 mg and 900 mg on QTc interval were studied and demonstrated minimal risk of QTc prolongation. 50 The FDA's review of this study concluded that a dose of 300 mg of solriamfetol (which is twice the highest FDA-approved dose) did not prolong the corrected QT interval by Fredericia (QTcF) to a clinically relevant extent. 1 There were no deaths with solriamfetol use in the 12week trials (TONES 2 and 3).…”
Section: Safety and Tolerabilitymentioning
confidence: 88%
“…15 Similar to findings with other wake promoting agents, cardiovascular safety reports have noted dose-dependent increases in blood pressure and heart rate with solriamfetol. Solriamfetol did not increase the QTcF interval > 10 ms in a study with healthy subjects at doses of 300 mg and 900 mg. 32 Secondary to the possible comorbidities present in individuals with OSA, a lower initial dose and frequent evaluation is warranted to minimize risk of major cardiovascular events. In the TONES 5 study, worsening of heart rate or blood pressure was not observed over 52 weeks.…”
Section: Safetymentioning
confidence: 99%